Patient Satisfaction and Loyalty in Public Healthcare: The Role of Digital Marketing and Service Quality - Rizka Amelia Mayasari; Basuki Rachmat (Journal of Business & Banking, 2025)
This study aims to analyze the effect of digital marketing and health service quality on patient satisfaction and loyalty at Rangkah health center, Surabaya. The background of this study is based on the increasing need for responsive, modern, and digital technology-based health services, especially in the context of competition with private health facilities. This study uses a quantitative approach with data collection techniques through questionnaires distributed to 179 respondents who have been treated at Rangkah health center. The analysis method used was Structural Equation Modeling-Partial Least Square (SEM-PLS). The results showed that both digital marketing and health service quality had a significant effect on patient satisfaction and loyalty. In addition, patient satisfaction was shown to act as a mediating variable between digital marketing and service quality with patient loyalty. These findings confirm the importance of integration between effective digital marketing strategies and improved service quality in building sustainable patient loyalty. This study provides strategic implications for public healthcare managers in the face of digital transformation in the healthcare sector.